A Comparison of the Effectiveness of the Reality-Based Acceptance and Commitment Therapy (RACT) Package and Cognitive-Behavioral Therapy (CBT) in Improving Procrastination and Responsibility in Adolescent Girls - Afshari, Mahbubeh; Khayatan, Floor; Yousefi, Zahra (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study aimed to investigate the effectiveness of the reality-based acceptance and commitment therapy package and cognitive-behavioral therapy in improving procrastination and responsibility in adolescent girls. Methods: The study was quasi-experimental with a pretest-posttest design, a control group, and a two-month follow-up. The statistical population consisted of all second-grade female students in District 5 of Isfahan in 2021. After screening with the academic burnout questionnaire, 45 adolescent girls were selected by the convenience sampling method and were randomly assigned to the experimental group of the reality-based acceptance and commitment therapy package (n=15), the experimental group of cognitive-behavioral therapy (n=15), and a control group (n=15). The experimental group received the researcher-made reality-based acceptance and commitment therapy package and another experimental group received cognitive-behavioral therapy for eight 90-minute sessions, and the control group did not receive any intervention. All three groups answered the Tuckman Procrastination Scale (1991), and California Responsibility Scale (1951) at three stages, pre-test, post-test, and follow-up. Data were analyzed using the repeated-measures mixed-model analysis of variance (ANOVA). Results: The Reality-Based Acceptance and Commitment Therapy Package affected the scores of procrastination (F= 8.9, P=0.007) and responsibility (F=9.40, P=0.004); and cognitive-behavioral intervention affected the score of procrastination (F=5.51, P=0.024) and responsibility (F=9.11, P=0.005), and the effects were stable at the follow-up stage. Conclusion: The research results suggest evidence that the researcher-made reality-based acceptance and commitment therapy package intervention and cognitive-behavioral therapy were appropriate methods to increase responsibility and reduce procrastination in adolescents.